2019
DOI: 10.1021/acs.jpcc.9b02320
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Broadband Responsivity of Ni-Doped Sb2Se3 Nanorod Photodetector

Abstract: Antimony selenide (Sb 2 Se 3 ) semiconductor with a narrow band gap is regarded as an ideal candidate for the next-generation broadband photodetectors. However, the photodetectors based on the binary Sb 2 Se 3 semiconductor suffer from low responsivity (R λ ) and external quantum efficiency due to the intrinsic low electrical conductivity. To address the issue, we introduce a low-valence Ni cation (Ni 2+ ) into the binary Sb 2 Se 3 ((Sb 1−x Ni x ) 2 Se 3 ) nanorods synthesized by a facile hot-injection process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Table summarizes some of the frequently used narrow-bandgap semiconductors and their bandgap values. Note that the chalcogenides (materials containing at least one chalcogen element, e.g., sulfur, selenium, or tellurium, as a substantial constituent, and at least one electropositive element), such as Ag 2 S, , Bi 2 S 3 , , MoS 2 , WS 2 , Sb 2 Se 3 , , In 2 Te 3 , account for a large proportion of narrow-bandgap semiconductors. They have also been directly utilized in photocatalysis to gain broadband photocatalytic activity.…”
Section: Strategies To Obtain Broadband G-c3n4-based Photocatalysts A...mentioning
confidence: 99%
“…Table summarizes some of the frequently used narrow-bandgap semiconductors and their bandgap values. Note that the chalcogenides (materials containing at least one chalcogen element, e.g., sulfur, selenium, or tellurium, as a substantial constituent, and at least one electropositive element), such as Ag 2 S, , Bi 2 S 3 , , MoS 2 , WS 2 , Sb 2 Se 3 , , In 2 Te 3 , account for a large proportion of narrow-bandgap semiconductors. They have also been directly utilized in photocatalysis to gain broadband photocatalytic activity.…”
Section: Strategies To Obtain Broadband G-c3n4-based Photocatalysts A...mentioning
confidence: 99%
“…In view of the existing effective recombination centers, [ 233 ] many studies have focused on strategies for inhibiting defects or incorporating impurities to elevate the Fermi level. [ 234–237 ] Following various approaches, including quasiepitaxy growth, surface sulfurization, and post‐treatment on Sb 2 S 3 films, the efficiency of Sb 2 S 3 ‐based solar cells can be improved by up to ≈7%. [ 238–240 ] Additionally, incorporating the effective impurities is also beneficial for increasing the carrier concentration.…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%
“…Thus, by mapping a series of materials, including PbX (X = S, Se, Te), Sb 2 Te 3 , Bi 2 X 3 (X = Se, Te), and inorganic halide perovskites, into a 2D space with the ES and ET as two coordinates, they found MVB had well‐defined borders to covalent, and iono‐covalent regions, indicating its distinction. [ 229–307 ] Such a map demonstrated that the MVB mechanism approximately possessed one shared electron and moderate electron transfer between adjacent atoms. This predictive model can also give rise to the favorable characteristics in above materials, including large Born effective charge, high optical dielectric constants, strong optical interband transition, etc.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…[ 14 ] 600–800% improvement of responsivity was realized in Se microtube photodetector by sputtering Au nanoparticles on surface of Se microtubes which had been reported by Hu et al. [ 15 ] In addition, strategies such as ion doping [ 16 ] and Schottky junction constructing [ 17 ] could also overcome the rapid recombination of photogenerated electron–hole pairs in photodetectors based on single material. Among these methods, heterojunction could effectively heighten the transportation and separation efficiency of charge carriers because a robust built‐in electric field would form at the heterojunction interface, leading to improved detection performance.…”
Section: Introductionmentioning
confidence: 99%